PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN SOSIOLOGI KELAS X FASE-EDI SMAN 1 GUNUNG TALANG - Susanti, Sari Kurnia; Yasin, Faishal; Wahyuni, Yanti Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning motivation of class X Phase E students in Sociology learning at SMAN 1 Gunung Talang. The aim of this research is to determine the effect of implementing the project based learning model on students' learning motivation. In this research, the theory used is constructivism theory according to Jean Piaget. This research method is quantitative research. This research data is in the form of an instrument containing data from respondents from the control class and experimental class. Where the experimental class was given treatment by applying a project based learning model, while the control class was treated with a conventional model. The population in this study were all class X students at SMAN 1 Gunung Talang. The sample for this research was 76 people. The sampling technique is purposive sampling technique. Data analysis techniques use Microsoft Excel software and SPSS version 3.1 software. The research results show that the project based learning model has a significant effect on learning motivation. Which is shown by the hypothesis test value, namely a significant value of 2 tailed 0.01 < 0.05. Based on the results of the research conducted, it can be concluded that the application of the project based learning model in Sociology learning can increase students' learning motivation.